Chorwaccy i serbscy wydawcy polskich książek dla dzieci i młodzieży w latach 1991–2022 - Ślawska, Magdalena (2023)
The aim of the article is to show how the repertoire of translations of Polish literature for children and young people in Croatia and Serbia has changed over the last thirty years. The author presents the changes that have taken place on the book market in both countries, and then shows which books by Polish authors are of particular interest to local publishers and turning points in the history of Polish children's books in these two countries in the analyzed period. The attention was focused on the activities of small publishing houses, which can be called “Lilliputians” such as: Srednja Europa and Planet Zoe from Croatia, and Propolis Books and Kozikas from Serbia. The text shows what quantitative and qualitative changes took place with the appearance of the above-mentioned publishers, who focus on children's literature of small languages, rarely found on bookstores. The analysis of their activities was carried out on the basis of Itamar Even-Zohar's theory of cultural repertoire, during which it was proved that the role played by these publishers in the process of shaping and modifying the repertoire of translations of Polish literature for children in both countries can be identified with the role of idea-makers.
Keywords: Polish literature for children and youth; translated literature; Croatian and Serbian Lilliputian publishers; theory of culture repertoire; idea-makers